Competition among native and invasive Impatiens species: the roles of environmental factors, population density and life stage - Čuda, Jan; Skálová, Hana; Janovský, Zdeněk; Pyšek, Petr (AoB PLANTS, 2015)
Many invasive species are considered competitively superior to native species, with the strongest competition expected in species with similar niches and/or in closely related species. However, competition outcome is strongly context-dependent as competitive strength varies along environmental gradients, and life stages, and also depends on abundances. To explore the importance of these factors, we examined competition effects in an experiment with three Impatiens species (Balsaminaceae) widespread in central Europe and sharing similar life-history characteristics and habitats: the native I. noli-tangere, and two invasive species, I. parviflora and I. glandulifera. We compared their competitive strength and reciprocal impacts under two levels of water and light availability, two overall planting densities and three competitor densities. We assessed species performance (ability to complete the life-cycle, biomass and fecundity) and temporal competition dynamics in a garden pot experiment. Environmental variables had lower explanatory power than overall planting and competitor density, which indicates the importance of competitive interactions when evaluating plant performance and potential invasion success. Despite poor and delayed germination, the invasive I. glandulifera attained dominance even at a high competitor density and was competitively superior across all treatments, exceeding the height of both congeners. Impatiens parviflora was competitively weakest, having a negligible impact on both native I. noli-tangere and invasive I. glandulifera. The intermediate competitive strength of the native I. noli-tangere probably results from its intermediate height, and good germination rate and timing. The difference in height among species increased during the experiment when I. glandulifera was involved; this species continues growing until autumn, enhancing its competitive superiority. The results provide a mechanistic understanding for the competitive exclusion of native I. noli-tangere that occurs in stands with I. glandulifera, but the limited impact of I. parviflora on I. noli-tangere in their mixed stands.
Keywords: congeners; plant density; Alien species; balsam; shading levels; competition; water availability